2021
DOI: 10.3389/fpsyg.2021.789413
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension Predictors in European Portuguese Adults

Abstract: Research on the predictors of reading comprehension has been largely focused on school-aged children and mainly in opaque orthographies, hindering the generalization of the results to adult populations and more transparent orthographies. In the present study, we aim to test two versions of the Simple View of Reading (SVR): the original model and an extended version, including reading fluency and vocabulary. Additional mediation models were analyzed to verify if other reading comprehension predictors (rapid aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…However, in an experiment which was more similar to our own, Ransby and Swanson (2003) found very little additional contribution of lower-level factors such as word reading and decoding (about 5% but significant) to explained variance. With skilled adult readers, Gonçalves et al (2021) also reported the influence of both high-level factors such as vocabulary and listening comprehension and low-level factors (such as word reading) on explaining text reading comprehension performance although the authors observed a greater explanatory power of the former. In our study, the questions used in the text reading comprehension test are implicit and explicit questions.…”
Section: Discussionmentioning
confidence: 97%
“…However, in an experiment which was more similar to our own, Ransby and Swanson (2003) found very little additional contribution of lower-level factors such as word reading and decoding (about 5% but significant) to explained variance. With skilled adult readers, Gonçalves et al (2021) also reported the influence of both high-level factors such as vocabulary and listening comprehension and low-level factors (such as word reading) on explaining text reading comprehension performance although the authors observed a greater explanatory power of the former. In our study, the questions used in the text reading comprehension test are implicit and explicit questions.…”
Section: Discussionmentioning
confidence: 97%
“…As far as the authors’ knowledge goes this is a pioneer study exploring early predictors of (un)success in reading acquisition with Portuguese-speaking children first graders that include sociodemographic, cognitive, and reading-related variables. Even the scarce literature focusing on reading predictors in Portuguese that previously exist does not focus on the early predictors of reading acquisition, instead focusing on the reading and cognitive variables in second grade ( Ziegler et al, 2010 ) or the precursors for reading comprehension with an adult population ( Gonçalves et al, 2021 ). This study is also a contribution to filling this gap and to the early identification of at-risk children (in this specific case right at the beginning of 1st grade).…”
Section: Discussionmentioning
confidence: 99%